1996
DOI: 10.1177/154193129604002403
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Communications and Situation Awareness (SA) in the Tactical Air-to-Air Environment

Abstract: Identifying and measuring behaviors consistently associated with situational awareness (SA) is frequently problematic. Though subtle, a person's SA may be reflected by how he/she communicates with other members of a team. Someone with high SA may not only provide different types of communication than someone with low SA, but also may exhibit different communication patterns (e.g., to whom).In the current study, we examined the communications of F-15 lead pilots who, along with an assigned wingman and ground co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…When the numbers of thought units in each category were transformed into a percentage of the total units communicated (see Table 4-4), the percentage of information request and response were found to significantly correlate to navigation errors, r = .93, p < .01 and r = .95, p < .01, respectively. Previous study by Hollenbeck et al (1995) Contrary to the findings by Hollenbeck et al (1995), Schreiber and colleagues (Schreiber et al, 1998;Schreiber et al, 1996) reported that high SA pilots requested more information. The latter finding is similar to the trend found in the enemy engagement task,…”
Section: Differences Across Teams Team Performancementioning
confidence: 66%
“…When the numbers of thought units in each category were transformed into a percentage of the total units communicated (see Table 4-4), the percentage of information request and response were found to significantly correlate to navigation errors, r = .93, p < .01 and r = .95, p < .01, respectively. Previous study by Hollenbeck et al (1995) Contrary to the findings by Hollenbeck et al (1995), Schreiber and colleagues (Schreiber et al, 1998;Schreiber et al, 1996) reported that high SA pilots requested more information. The latter finding is similar to the trend found in the enemy engagement task,…”
Section: Differences Across Teams Team Performancementioning
confidence: 66%